NAPOLEON AND THE OPERATIONAL ART OF WAR : essays in honor of donald d. horward. (BRILL, 2020)
In this revised and extended edition of 'Napoleon and the Operational Art of War', the leading scholars of Napoleonic military history provide the most authoritative analysis of Napoleon's battlefield success and ultimate failure. Napoleon's development and mastery of the operational art of warfare is revealed as each chapter analyzes one Napoleonic war or major campaign of a war. To achieve this, the essays conform to the common themes of Napoleon's planning, his command and control, his execution of plans, and the response of his adversaries. Napoleon's sea power and the British response to the French challenge at sea is also investigated. Overall, this volume reflects the finest scholarship and cutting-edge research to be found in Napoleonic Military History.